TOTAL NILAI EKOSISTEM MANGROVE DI KABUPATEN GORONTALO UTARA, PROVINSI GORONTALO - Riesti Triyanti; Maulana Firdaus; Radityo Pramoda (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2017)
Mangrove forest is the main life-supporting ecosystem in coastal and marine areas. Little information is available on quantifying of mangrove function as well as its benefit. The study is conducted to quantify the totalvalue of the mangrove ecosystem in North Gorontalo Regency. Data were collected through interviews with users and non-users of the resources along with secondary data such as the amount of carbon storage and cost of standard construction of break water for mangrove ecosystem. Data were analyzed by using economic valuation techniques for calculating total value of the mangrove ecosystem. The results showed that the ecological valuewas Rp18,205,000,890/hectare/year, the economic value was Rp40,716,063/hectare/year, while the social and cultural values was Rp20,341,259/hectare/year. Hence, the total value of mangrove ecosystem in North Gorontalo Regency amounts to Rp18,266,058,212/hectare/year. This shows the importance of the mangrove resources in term of its values that needs to be informed to the decision-makers, so that it can be managed in a sustainable way with proper benefits and costs consideration.